2014
DOI: 10.1098/rspb.2014.0281
|View full text |Cite
|
Sign up to set email alerts
|

Sexual conflict over mating in Gnatocerus cornutus ? Females prefer lovers not fighters

Abstract: Female mate choice and male-male competition are the typical mechanisms of sexual selection. However, these two mechanisms do not always favour the same males. Furthermore, it has recently become clear that female choice can sometimes benefit males that reduce female fitness. So whether malemale competition and female choice favour the same or different males, and whether or not females benefit from mate choice, remain open questions. In the horned beetle, Gnatocerus cornutus, males have enlarged mandibles use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 88 publications
1
48
0
Order By: Relevance
“…This suggests that males who win fights may not also be able to achieve high mating success under female choice. A similar conclusion was reached in a recent study investigating female preference for morphological traits known to be associated with fighting success in this species (Okada et al ., ). The authors found that females chose mates not on the basis of fighting traits but rather on male courtship rate, and consequently, mating success was not correlated with fighting success.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that males who win fights may not also be able to achieve high mating success under female choice. A similar conclusion was reached in a recent study investigating female preference for morphological traits known to be associated with fighting success in this species (Okada et al ., ). The authors found that females chose mates not on the basis of fighting traits but rather on male courtship rate, and consequently, mating success was not correlated with fighting success.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless even when mechanisms of sexual selection are antagonistic and females do not exert a preference for dominant males, it remains possible for dominant males to gain a mating advantage over their competitors through force or coercion, increasing their own mating opportunities and ultimately overriding female mate choice (Qvarnstr枚m & Forsgren, ; Wong & Candolin, ). Evidence of conflict between male鈥搈ale competition and female mate choice has been observed in flour beetles (Harano et al ., ; Yamane et al ., ; Okada et al ., ), cockroaches (Moore & Moore, ), bitterlings (Reichard et al ., ; Casalini et al ., ), brown trout (Petersson et al ., ) and water striders (Sih et al ., ). The consequences of mating with dominant, nonpreferred males can be severe, for example female cockroaches Nauphoeta cinerea mated to nonpreferred males had a reduced lifespan and produced fewer offspring (Moore et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…; Okada et al . ). There is also evidence that mandible size trades off with other cephalic characters, such as the head horns, antennae and eyes (Okada & Miyatake ).…”
Section: Introductionmentioning
confidence: 97%
“…Although mate-choice benefits via the Fisherian process have been well demonstrated in numerous taxa (e.g., Brooks & Endler, 2001;Taylor et al, 2007;Potti & Canal, 2011;Suzaki et al, 2013;Okada et al, 2014), relatively few studies have successfully detected the benefits related to good male genes (but see Moore, 1994;Hoikkala et al, 1998;Hoefler et al, 2009;Garcia-Gonzalez & Simmons, 2011;Simmons & Holley, 2011). A meta-analysis of indirect benefits suggested that the effect of good genes on the evolution and maintenance of female preference is relatively smaller than that of the Fisherian model (M酶ller & Alatalo, 1999;Prokop et al, 2012).…”
Section: Introductionmentioning
confidence: 99%